Analysis of Pectin Levels in Banana Kepok (Musa paradisiaca) and Banana Raja (Musa sapientum) - Timang, Selfiana Imu; Sabang, Sri Mulyani; Ratman, Ratman (Jurnal Akademika Kimia, 2019)
Banana is a type of fruit that is relative widely consumed by community, either directly consumed or processed into other foods such as fried bananas and chips, while the peelsare usually thrown as waste. Banana peel is one source of pectin. Pectin is a polymer of D-galactaconic acid linked by an Î±-1,4-glycosidic bond. Pectin compounds are widely used in pharmaceutical, food, and beverage industries. This study aimed to determine pectin levels in banana peel and banana raja. This study was done by extraction method using HCl, added with 96% ethanol to filtrate to precipitate the pectin, then dried to obtain dry pectin. The solvent used was 0.05 N HCl (pH 1.5) with extraction temperature 90 for 80 minutes. The results showed that the extraction of banana kepok peel produced 12.243% pectin, while the extraction of banana raja peel produced 6.383% pectin.